The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/biosci/bix133
|View full text |Cite|
|
Sign up to set email alerts
|

Internet Blogs, Polar Bears, and Climate-Change Denial by Proxy

Abstract: Increasing surface temperatures, Arctic sea-ice loss, and other evidence of anthropogenic global warming (AGW) are acknowledged by every major scientific organization in the world. However, there is a wide gap between this broad scientific consensus and public opinion. Internet blogs have strongly contributed to this consensus gap by fomenting misunderstandings of AGW causes and consequences. Polar bears (Ursus maritimus) have become a “poster species” for AGW, making them a target of those denying AGW evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 49 publications
0
41
0
1
Order By: Relevance
“…It is also the means of establishing a controversy.” Begley (2007) refer to the “paralyzing fog of doubt around climate change”. This doubt takes three main thrusts: doubt about the reality of climate change, doubt about the urgency, and doubt about the credentials of climate scientists (Boussalis & Coan, 2018; Dunlap & McCright, 2011; Harvey et al, 2018; Moser, 2010).…”
Section: Why Does Misinformation About Climate Change Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the means of establishing a controversy.” Begley (2007) refer to the “paralyzing fog of doubt around climate change”. This doubt takes three main thrusts: doubt about the reality of climate change, doubt about the urgency, and doubt about the credentials of climate scientists (Boussalis & Coan, 2018; Dunlap & McCright, 2011; Harvey et al, 2018; Moser, 2010).…”
Section: Why Does Misinformation About Climate Change Matter?mentioning
confidence: 99%
“…A summary of the potential ways to counteract misinformation found in the literature, along with their criticisms and caveats [1: Cook et al, 2018; 2: Zucker, 2019; 3: Roozenbeek & van der Linden, 2019; 4: Epstein et al, 2019; 5: Lutzke et al, 2019; 6: Sullivan et al, 2014; 7: Hess & Collins, 2018; 8: Bedford, 2010; 9: Bedford et al, 2014; 10: Bedford & Cook, 2013; 11: Legates et al, 2013; 12: Legates et al, 2015; 13: McNeal et al, 2014; 14: Cook et al, 2017; 15: Cook et al, 2015; 16: van der Linden et al, 2017; 17: Shao, Ciampaglia, et al, 2018; 18: Safieddine et al, 2016; 19: Pennycook & Rand, 2019; 20: Fernandez & Alani, 2018; 21: Vicario et al, 2016; 22: Leetaru, 2018; 23: Pew Research Center, 2017; 24: Mavrovic, 2018; 25: Henley, 2018; 26: European Commission, 2018; 27: Lawrence & Estow, 2017; 28: Kahan, 2017; 29: Benegal & Scruggs, 2018; 30: Harvey et al, 2018; 31: Nyhan & Reifler, 2010; 32: Garrett & Weeks, 2013; 33: Anderson et al, 1980; 34: Thorson, 2016; 35: Funke, 2019; 36: ALA, 2019; 37: Tompros et al, 2017]…”
Section: What Can Be Done About Misinformation About Climate Change?mentioning
confidence: 99%
“…identified that such professional news and weather agencies played a dominant role as information sources and information diffusers to the public (Kim et al , ). However, blog owners that deny or downplay global warming attempted to disregard the overwhelming scientific evidence, such as Arctic sea‐ice loss and polar bear vulnerability, to cast doubt on other established ecological consequences of global warming, thereby aggravating the consensus gap (Harvey et al , ). A case study on the question–answer community Quora also suggests that emphasis on specific subjects but not popular knowledge of climate change could draw more public attention on the issue of climate change (Jiang et al , ).…”
Section: Review Of Previous Work and Analysismentioning
confidence: 99%
“…This blog post has several links back to polarbearscience.com, including a link to a page with Crockford's publications, in an attempt to represent her as a neutral scientist and her attackers as biased. The post is a response to a Bioscience article on blogs and climate change denial (Harvey et al, 2018), and while the Bioscience article is discussed and debated, it is not linked to, nor is a complete citation provided.…”
Section: Networked Spacementioning
confidence: 99%